2018
DOI: 10.1002/adom.201800333
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastable Fluorescent Polymer Dots for Stimulated Emission Depletion Bioimaging

Abstract: used fluorophores, such as organic dyes and fluorescent proteins. This severely limits STED nanoscopy for long-term observation of cellular events. [2] Moreover, the lateral spatial resolution of STED nanoscopy is theoretically depend on STED beam intensity, with a higher intensity resulting in a better resolution. [3] Therefore, highly photostable fluorophores are urgently desired for the wide application of STED imaging.Besides the efforts to develop more photostable dye molecules, in recent years, the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…Fluorescent semiconductor polymer dots (Pdots) can also be used as STED probes thanks to their high brightness, photostability, and low cellular toxicity. Wu et al adopted Pdots for STED imaging and demonstrated high biocompatibility, photostability, and good depletability [ 110 ]. Pdots could be conjugated with molecules such as biotin and showed a very low STED power requirement (<3 mW for 70 nm resolution).…”
Section: Progress In Development Of Fluorescent Probes For Sted Nanoscopymentioning
confidence: 99%
“…Fluorescent semiconductor polymer dots (Pdots) can also be used as STED probes thanks to their high brightness, photostability, and low cellular toxicity. Wu et al adopted Pdots for STED imaging and demonstrated high biocompatibility, photostability, and good depletability [ 110 ]. Pdots could be conjugated with molecules such as biotin and showed a very low STED power requirement (<3 mW for 70 nm resolution).…”
Section: Progress In Development Of Fluorescent Probes For Sted Nanoscopymentioning
confidence: 99%
“…However, it remains challenging to find a class of STED nanoprobes that fulfill all these requirements in practice. For recently emerged STED nanoprobes, including quantum dots, polymer nanoparticles, aggregation‐induced emission nanoparticles, and upconversion nanocrystals, despite their distinct features, they still suffer intrinsic limitations such as large physical dimensions, high saturation intensity or low lateral resolution.…”
Section: Figurementioning
confidence: 99%
“…Alternatively, hydrophobic polymers exhibiting TADF can be coprecipitated with amphiphilic polymers in water, giving luminescent nanoparticles termed polymer dots (Pdots). Pdots are water‐soluble nanoparticles containing ≥50 % semiconducting polymer by weight or volume, [20] and have emerged as powerful probes for bioimaging, [20–26] biosensing, [27–30] and photodynamic therapy [31–33] . Characterized by improved photostability and high brightness, Pdots can also be functionalized for cell targeting and therapy, providing a versatile platform for theranostics [34] .…”
Section: Introductionmentioning
confidence: 99%
“…Pdots are water-soluble nanoparticles containing ! 50 %semiconducting polymer by weight or volume, [20] and have emerged as powerful probes for bioimaging, [20][21][22][23][24][25][26] biosensing, [27][28][29][30] and photodynamic therapy. [31][32][33] Characterized by improved photostability and high brightness,P dots can also be functionalized for cell targeting and therapy, providing aversatile platform for theranostics.…”
Section: Introductionmentioning
confidence: 99%